Pore pressure modeling in central area of santos basin, Brazil - Picolini, João Paulo; Chang, Hung Kiang [UNESP] (My University, 2019)
Pore pressures (PP) have been studied in a central area of the Santos Basin, Brazil, Special attention was given to the K90 Depositional Sequence, Santonian to Campanian age, composed by two formations-Juréia and Itajaí-Açu. The last is made of pelitic rocks (Shale-Seal) and sandstones (Main Reservoir) with gas accumulations. The 1D models allowed to quantify pore pressures, verify their distribution and suggest probable causes for overpressure (anormal high pressure). A Main Zone of Anormal High Pressure (ZPA) and a Secondary ZPA were detected in the K90 Sequence and, zones of minor importance (ZPA-2a e ZPA-2b), were detected in the older sequences (K82-86 and K88). The Main ZPA encompass the Main Accumulation of gas of the area (800m of thickness) and presents a pore pressure gradient (GPP) up to 12,6 ppg (gas zone) and 11,7 ppg (water zone). Gas is the main element to generate overpressure. PP has raised up in the gas zone (buoyance effect) and Gas and water coexistence must have reduced the hydraulic conductivity of the Shale-Seal, retarding equalization of the pressures. Less permeable layers and sealing faults further reduced the flow of fluids, contributing to the elevation of pore pressures.
Modelagem de pressões de poros na área central da bacia de santos
Keywords: Overpression; Petroleum; Pore pression; Santos Basin; Well log profiles